DIFFERENTIAL REGULATION OF PC1/3, PC2 AND PHOSPHORYLATED CREB BY SHORT-TERM AND LONG-TERM MORPHINE TREATMENT: IMPLICATIONS FOR UNDERSTANDING THE “SWITCH” TO OPIATE ADDICTION - ESPINOSA, VERONICA PAEZ (2008)
Drug addiction is a state of altered brain reward and self-regulation mediated by both neurotransmitter and hormonal systems. Although an organism’s internal system attempts to maintain homeostasis when challenged by exogenous opiates and other drugs of abuse, it eventually fails, resulting in the transition from drug use to drug abuse. We propose that the attempted maintenance of hormonal homeostasis is achieved, in part, through alterations in levels of processing enzymes that control the ratio of active hormone to pro-hormone. Two pro-hormone convertases, PC1/3 and PC2 are believed to be responsible for the activation of many neurohormones and expression of these enzymes is dependent on the presence of a cyclic-AMP response element (CRE) in their promoters. Therefore, we studied the effects of short-term (24-h) and long-term (seven-day) morphine treatment on the expression of hypothalamic PC1/3 and PC2 and levels of phosphorylated cyclic-AMP-response element binding protein (P-CREB). While short-term morphine exposure down-regulated, long-term morphine exposure up-regulated P-CREB, PC1/3 and PC2 protein levels in the rat hypothalamus as determined by Western blot analysis. Quantitative immunofluorescence studies confirmed these regulatory actions of morphine in the paraventricular and dorsomedial nucleus of the hypothalamus. Specific radioimmunoassays demonstrated that the increase in PC1/3 and PC2 levels following long-term morphine led to increased TRH biosynthesis as evidence by increased TRH/5.4 kDa C-terminal proTRH-derived peptide ratios in the median eminence. Promoter activity experiments in rat sommatomammotrope GH3 cells containing the mu-opioid receptor demonstrated that the CRE(s) in the promoter of PC1/3 and PC2 is required for morphine-induced regulation of PC1/3 and PC2. Our data suggest that the regulation of the prohormone processing system by morphine may lead to alterations in the levels of multiple bioactive hormones and may be a compensatory mechanism whereby the organism tries to restore its homeostatic hormonal milieu. The down-regulation of PC1/3, PC2 and P-CREB by short-term morphine and up-regulation by long-term morphine treatment may be a signal mediating the switch from drug use to drug abuse.